2022
DOI: 10.17485/ijst/v15i23.493
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrical Output in Photogalvanic Cell for Solar Energy Conversion and Storage: Lauryl Glucoside-Tartrazine-D-Fructose System

Abstract: Objective: The present study is focusing on the role of surfactant in photogalvanic cells and how photons from sunlight can be used as a driving force for energy solar energy conversion and storage. Methods: An H shaped cell was designed for study of electrical output in solar transformations. Electrical circuit was proposed by using of dye, reductant, surfactant, NaOH, double distilled water (DDW), multi-meter, calomel electrode, 250 k roistered, saturated calomel electrode, platinum electrode, carbon pot, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…EDTA+TB+NaLS PG cell fill factor was 0.3670 and previously reported fill factor were 0.211, 0.200, 0.240 and 0.207 (Koli et al, 2021) . Whereas, the maximum photocurrent observed was at 150.00 uA in EDTA+TB+NaLS PGS, and already reported results were 190 uA (Rathore et al 2022). Thus the impact of solar energy was studied by varying the various parameters in PG cell.…”
Section: Importance Of Worksupporting
confidence: 63%
See 3 more Smart Citations
“…EDTA+TB+NaLS PG cell fill factor was 0.3670 and previously reported fill factor were 0.211, 0.200, 0.240 and 0.207 (Koli et al, 2021) . Whereas, the maximum photocurrent observed was at 150.00 uA in EDTA+TB+NaLS PGS, and already reported results were 190 uA (Rathore et al 2022). Thus the impact of solar energy was studied by varying the various parameters in PG cell.…”
Section: Importance Of Worksupporting
confidence: 63%
“…Thus the impact of solar energy was studied by varying the various parameters in PG cell. Conclusively, the currently observed PG cell performance is relatively higher than the reported PG systems (5,8,9) . The effects will be made to develop the PG cell having higher electrical output than the already reported results (see reference no., (5,8,10) ).…”
Section: Importance Of Workmentioning
confidence: 58%
See 2 more Smart Citations
“…Later on Meena et al, observed the photochemical degradation of dye 10 , Yadav et al, studied photo reduction of methylene blue and Safranine O in EDTA 11 . Rathore et al, 12,13 the shortlived processes in PG cells for solar power generation and storage. Rathore and Lal studied photogalvanics for comparative better electrical output 14 .…”
Section: Introductionmentioning
confidence: 99%